KONSEP PERANCANGAN TAMAN REKREASI DAN OLAHRAGA DI KELURAHAN BALEARJOSARI KOTA MALANG - Angwarmas, Faustinus; Setyabudi, Irawan (Aksen : Journal of Design and Creative Industry, 2020)
Open space is a space that is used for joint activities in the open air, while the kinds are green open spaces and built-in open spaces (public and private). A space will have meaning if there is human activity in it and not only as an abandoned space. In this study, an open space design was carried out, with changes in the land use function of agricultural land. Park area designed for 3,100 m2. After discussing with local residents, sports facilities are needed in Balearjosari Village. The reason for choosing the location is that the surrounding conditions are still natural and in the countryside so that it attracts visitors to the area. Another facility needed is a recreation area in the form of a children’s playground. This study aims to create the concept of Balearjosari park as recreation and sport with a landscape architecture approach. The research method used the design method as a development of the theory of Gold (1988) and Hakim (2012), namely by the stages of survey and interview, analysis and synthesis, ideas and continued with the design concept. The results in this study are in the form of various concepts consisting of basic concepts, form concepts, space concepts, circulation concepts, activity and facilities concepts, vegetation concepts, and material concepts. Its novelty value is solving problems according to the needs of the park in that location, making it different from other areas. The conclusion is that the solutions offered by landscape architects can provide an overview to the community in the form of recreational and educational park design concepts, according to community needs. Keywords: Concept, Parks, Recreation and Educationt, Balearjosari